Energy performance evaluation of R1234yf, R1234ze(E), R600a, R290 and R152a as low-GWP R134a alternatives. (February 2017) - Sánchez, D.; Cabello, R.; Llopis, R.; Arauzo, I.; Catalán-Gil, J.; Torrella, E.
Highlights: A refrigerating facility was experimentally tested with five low-GWP alternatives. The results had been compared with R134a in the same operating conditions. R290 presented an increment of COP, cooling capacity and compressor power consumption. R152a and R1234yf presented a slight variation in terms of COP and cooling capacity. R600a and R1234ze(E) presented an important reduction in cooling capacity and COP. Abstract: In 2014, the Directive 517/2014 was introduced by European Parliament to reduce the use of high-GWP greenhouse gases in the European area in order to limit global climate change in accordance with the objectives marked by the EU Research and Innovation programme Horizon 2020. These restrictions affect the large majority of artificial refrigerants among which R134a is included due to its relatively high GWP100 (1301). The widely used of R134a in the refrigeration and air conditioning fields reveals the need to identify new low-GWP alternatives. Accordingly, in this work five low-GWP R134a possible choices have been tested and compared in an identical refrigerating facility equipped with a hermetic compressor, under the same operating conditions. The refrigerants used in this analysis are: R290 and R600a (HCs); R134a and R152a (HFCs), and finally, R1234yf and R1234ze(E) (HFOs). All of them have been assayed without changes in the facility, that is, as direct drop-ins . The results obtained from the experimental tests are presented and commented in this work from the energetic point of view.